Diversidade de recursos florais para beija-flores nos cerrados do Triângulo Mineiro e região - Machado, Adriana de Oliveira (2012)
The open savanna areas of the Cerrado region in Central Brazil have been considered as marginal or complementary habitats to hummingbirds, even with a relatively small number of truly ornithophillous plant species. The structural and climatic conditions would explain the low number of ornithophilous species, which are better represented in forest environments, being the Atlantic forest the Brazilian biome with the greatest number of hummingbird pollinated species. The mutualistic interactions between plants and pollinators seem to be important for the evolution and maintenance of biodiversity, in such a way that modern methods and metrics for the analysis of these networks have been used to understand the organization of species in such communities. The objective of the present study was to describe the interaction between hummingbirds and plants in three cerrado areas, the Panga Ecological Station and the Clube de Caça e Pesca Itororó de Uberlândia, in Uberlândia, MG, and the Serra de Caldas Novas State Park, in Caldas Novas, GO. In each area there were used two transects of one hectare each, which were followed every other week to identify the plant species used by hummingbirds. The number of individuals and flowers were recorded and the distribution pattern along the transects were analyzed. The nectar was analyzed in order to estimate the amount of energy available for the hummingbirds during the study. Hummingbird species were identified and their visiting behavior was observed. Based on field data and literature records, the interaction networks between hummingbirds and plants for each area were built and analyzed. The number of plant species offering nectar for the hummingbirds (26) was higher than observed for other studies in the same areas but was lower than the ones recorded for tropical forest habits. Only nine species presented ornithophilous syndrome. The Vochysiaceae was the most representative family as a whole, and the Bromeliaceae and Rubiaceae were the most important among the truly ornithophilous. Most families were represented by a few genera and species, as in most hummingbird flora studies to date, supporting the idea of diffuse coevolution between these birds and plants. Among the non-ornithophilous plants, most have yellow flowers with gullet or flag corolla while among the ornithophilous, the tubular, red or yellow flowers predominate. Most ornithophilous plants were herbs while the non-ornithophilous were mostly trees. There were 13 hummingbird species among the three areas, most of the subfamily Trochilinae, a number of species greater than observed in study of pollination in most environments, including Tropical Forest areas. The relatively small number of truly ornithophilous species in the Brazilian savanna may cause the hummingbirds to visit many flowers with morphology adapted to other pollinators. Despite the morphological differences, the nectar features of ornithophilous and non-ornithophilous flowers were not significantly different. Although the Cerrado flora has been characterized by its high β-diversity, the transects and areas were very similar both for the plants used by hummingbirds and for the resource availability pattern. The interaction networks showed asymmetry and nestedness patterns similar to the described for other mutualistic networks, with average of connectance of 38%, even greater than observed for other plant/pollinator networks. Palicourea rigida was the most important plant species for the hummingbirds in most areas and Amazilia fimbriata was the hummingbird that visited the greatest number of plant species.